Abediterol, a novel long-acting β2-agonist: bronchodilation, safety, tolerability and pharmacokinetic results from a single-dose, dose-ranging, active-comparator study in patients with COPD. Issue 1 (December 2016) - Beier, Jutta; Pujol, Helena; Seoane, Beatriz; Jimenez, Eulalia; Astbury, Carol; Massana, Eric; Ruiz, Sandrine; de Miquel, Gonzalo
Abstract Background Abediterol is a novel, once-daily long-acting β2 -agonist in development for the treatment of chronic obstructive pulmonary disease (COPD) and asthma in combination with an anti-inflammatory agent. This Phase IIa, randomised, double-blind, crossover study investigated the bronchodilation, safety, tolerability and pharmacokinetics of abediterol in patients with moderate to severe COPD. Methods Seventy patients (aged ≥40 years, Global initiative for chronic Obstructive Lung Disease Stage II/III) were randomised (1:1:1:1:1:1) to single doses of abediterol 0.625, 2.5, 5 or 10 μg, indacaterol 150 μg or placebo. Spirometry was performed up to 36 h post-dose. Pharmacokinetics were assessed in a subset of patients (N  = 20). Safety and tolerability were evaluated throughout the study. Results Abediterol (all doses) significantly improved change from baseline in trough forced expiratory volume in 1 s (FEV1 ) compared with placebo (0.102, 0.203, 0.233 and 0.259 L for abediterol 0.625, 2.5, 5 and 10 μg, respectively; allp  < 0.0001; primary endpoint). Abediterol 2.5, 5 and 10 μg significantly improved trough FEV1 compared with indacaterol 150 μg (0.092, 0.122 and 0.148 L, respectively; allp  < 0.0001). Improvements in bronchodilation were maintained at all time points post-dose versus placebo (all abediterol doses) and from 15 or 30 min post-dose versus indacaterol 150 μg with abediterol 2.5, 5 and 10 μg (allp  < 0.05). Abediterol had low systemic exposure; incidence of treatment-emergent adverse events was similar between treatment groups. Conclusions All doses of abediterol (0.625–10 μg) provided clinically and statistically significant, dose-dependent improvements in bronchodilation versus placebo, and abediterol 2.5, 5 and 10 μg gave significant improvements versus indacaterol. All doses of abediterol were safe and well tolerated in patients with COPD. Trial registration Clinicaltrials.govNCT01425814 . Registered 29 August 2011.